Myostatin serum concentration as an indicator for deviated muscle metabolism in severe burn injuries. (December 2019) - Wallner, C.; Wagner, J. M.; Dittfeld, S.; Drysch, M.; Lehnhardt, M.; Behr, B.
Introduction: Patients experiencing thermal injuries with an extent of over 20% of total body surface area suffer from systemic catabolic disease. The thermal trauma-induced loss of muscle mass causes a higher incidence for comorbidities and subsequently a higher mortality. In this study, we aimed to investigate the role of myostatin in the interplay with follistatin during muscle cachexia. Methods: Patients with burn injuries (>10% total body surface area) between the ages of 18 and 75 were prospectively included within the first 48 h after trauma to determine deviations of parameters connected to muscle catabolism. In the chronic state of burn injury (9–12 months after trauma), we re-evaluated myostatin and follistatin concentrations as well as muscle strength of the non-dominant forearm. Results: We were able to show a time-dependent alteration (9–12 months after burn injury) of myostatin with an initial decrease ( p < 0.001) and long-term increase ( p < 0.001) after thermal injury in blood serum. For follistatin, a reciprocal correlation was observed ( r = −0.707, p = 0.001). Accordingly, muscle strength of the non-dominant hand and forearm was significantly decreased 9–12 months after injury in post-burn patients compared with healthy patients with a significant correlation to myostatin levels ( r = −0.899, p < 0.001). In addition, initial myostatin serum concentration was predictive for long-term muscle strength impairment. Conclusion: With regard to the muscle metabolism after thermal trauma, our data suggest an acute anabolic response, presumably to spare muscle mass, which is converted to catabolic conditions accompanied by muscle strength reduction in the chronic phase. Myostatin plays a crucial role in this orchestration and initial myostatin concentration may predict the long-term muscle strength.